Monetary policy announcements and stock market reactions : Evidence from the Finnish stock markets in 2000-2022 - Huotari, Jaakko (My University, 2024)
After the global financial crisis in 2008, the monetary policy of central banks has changed dramatically, and especially in recent years, unconventional monetary policy actions have played a more central role in the monetary policy pursued by central banks around the world. Quantitative easing and historically low interest rates have directed capital to riskier investments such as the stock market. This thesis examines the relationship between the European Central Bank monetary policy and the Finnish stock market, focusing especially on the short-term effects that monetary policy announcements have on the Finnish stock market. Daily stock index returns are used as a measure for reactions. The research has been conducted as an event study, which examines the effect of individual events on changes in the share price. The event window is three days around monetary policy announcements, the day before, the day of the announcement, and the day after the announcement. Each monetary policy announcement is treated as its own event, and for each announcement, abnormal return from what is expected is calculated. The research material needed for the study has been compiled manually by going through all the monetary policy announcements of the European Central Bank from 2000 to 2022, and the monetary policy announcements have been divided into four categories: no changes in interest rates, interest rate increases, interest rate decreases, and unconventional monetary policy actions taken in the announcement. In addition to this, the data set contains 5778 daily observations of the OMXHPI price index of the Helsinki Stock Exchange. Based on the data, abnormal returns are calculated for each of the three days, and cumulative abnormal returns are calculated for the entire event window. The statistical significance of the abnormal returns obtained from each announcement is tested with a t-test. The statistical significance of average abnormal returns is tested over the entire data period through the examination of cumulative returns of individual days and the event window. This is done by using the average abnormal return in a t- test, and the average cumulative abnormal return is analyzed in the same way. Corresponding average abnormal returns are also calculated for market sentiments (bull and bear market) and monetary policy direction cycles (tightening and loosening monetary policy) to determine the effects of different market sentiments and monetary policy direction trends on the stock index. The findings of this thesis show that during the three-day event window, the cumulative abnormal returns are statistically significant, while the individual days during the event window are not found to result in statistically significant abnormal returns. Market sentiment was found to be a significant factor in how the markets react to monetary policy announcements. The direction of monetary policy is also a significant factor in explaining market reactions; loosening monetary policy creates significant abnormal returns, while this was not found for tightening policy. Significant evidence of abnormal returns resulting from certain types of monetary policy actions during the event window was not found.

Vuoden 2008 globaalin finanssikriisin jälkeen keskuspankkien rahapolitiikka on muuttunut dramaattisesti ja erityisesti viime vuosien aikana epätavanomaiset rahapoliittiset toimet ovat näytelleet keskeisempää roolia keskuspankkien harjoittamassa rahapolitiikassa. Määrällinen elvytys ja historiallisen alhaiset korkotasot ovat ohjanneet pääomia riskialttiimpiin sijoituksiin kuten osakemarkkinoille. Tässä tutkielmassa tutkitaan Euroopan keskuspankin rahapolitiikan ja Suo- men osakemarkkinoiden suhdetta, keskittyen erityisesti lyhytaikaisiin vaikutuksiin, joita rahapo- liittisilla ilmoituksilla on Suomen osakemarkkinoille. Reaktioiden mittarina käytetään päivittäisiä osakeindeksin tuottoja. Tutkimus on toteutettu tapahtumatutkimuksena (engl. Event study) jolla tutkitaan yksittäisten tapahtumien vaikutusta osakkeiden hinnan muutoksiin. Tapahtumaikkuna on kolme päivää rahapoliittisten ilmoitusten ympärillä, päivä ennen, ilmoituspäivä sekä ilmoituksen jälkeinen päivä. Jokainen rahapoliittinen ilmoitus käsitellään omana tapahtumanaan ja jokaiselle ilmoitukselle lasketaan odotetusta tuotosta poikkeava tuotto. Tutkimusta varten tarvittava tutkimusaineisto on koostettu manuaalisesti läpikäymällä kaikki Euroopan Keskuspankin rahapoliittiset ilmoitukset vuosien 2000–2022 ajalta ja rahapoliittiset ilmoitukset on jaettu neljään kategoriaan: ei muutoksia koroissa, koron nosto, koron lasku ja epätavanomaiset rahapoliittiset toimet, joita ilmoituksella on ilmoitettu. Tämän lisäksi aineisto sisältää 5778 päivittäistä havaintoa Helsingin pörssin hintaindeksi OMXHPI:stä. Aineiston pohjalta jokaiselle kolmelle päivälle lasketaan odotuksesta poikkeavat tuotot ja koko tapahtumaikkunalle lasketaan kumulatiivinen poikkeava tuotto. Jokaisesta ilmoituksesta saatava poikkeava tuoton tilastollinen merkitsevyys testataan t-testillä. Yksittäisten päivien sekä tapahtumaikkunan kumulatiiviset tuotot testataan myös keskimääräistä poikkeavaa tuottoa hyödyntäen siten, että koko aineiston ajalta laskettujen poikkeavien tuottojen keskiarvon tilastollinen merkitsevyys testataan t-testillä ja keskimääräinen kumulatiivinen poikkeava tuotto testataan samoin. Vastaavat keskimääräiset poikkeavat tuotot lasketaan myös markkinasentimenteille (härkä ja karhumarkkina) sekä rahapolitiikan suunnan sykleille (tiukentava ja löysentävä rahapolitiikka) jotta eri markkinasentimenttien ja rahapolitiikan suunnan trendin vaikutuksia voidaan selvittää. Tutkimuksen tuloksista huomataan, että käsitellyn kolmen päivän aikaikkunan kumulatiiviset tuotot poikkeavat tilastollisesti merkittävästi odotetusta tuotosta, mutta yksittäisten päivien tuotot eivät poikkea merkittävästi odotuksista. Markkinasentimentin huomattiin olevan merkittävä tekijä siinä, miten markkinat reagoivat rahapoliittisiin ilmoituksiin. Myös rahapolitiikan suunta on merkittävä tekijä markkinareaktioiden selittäjänä; löysentävä rahapolitiikka tuottaa merkittäviä poikkeavia tuottoja, kun tiukentavan politiikan osalta tätä ei havaittu. Todisteita tietynlaisten rahapoliittisten toimien aiheuttamista poikkeavista tuotoista kolmen päivän aikaikkunan aikana ei löydetty.
Keywords: rahapolitiikka; arvopaperimarkkinat; pörssit; keskuspankit; central banks; monetary policy; stock prices; interest policy; announcements; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; Master's Degree Programme in Finance